THE EFFECT OF TECHNOLOGICAL CAPITAL DISCLOSURE ON MANUFACTURING COMPANIES EMPLOYEES - Chintya Wangsih, Ingkak; Pane, Zulfikar Ikhsan (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
Technological transformation is mandatory for companies sustainability, but unfortunately it has potential negative impact on employees. This research examines the impact of technological capital disclosure on the number of employees and salary expenditure by expansive test. Using secondary data of 366 observations and 371 observations of expansive test with manufacturing industrial companies in 2015 - 2020, it was found that technological capital had a significant negative impact on the number of employees and salaries expenditure2. These results show highly technology used and the presence of directors with technical/technology education backgrounds can reduce number of employees and salary costs. For this reason, research contribution is additional consideration for companies director when investing in technology so the benefits are equally received by companies and employees, for example through technology training and similar development of human resources.